Semioses da fotoperformance de Berna Reale em perspectiva barthesiana - Vasconcelos, Juliana Medeiros (2023)
This research focuses on a reflection on the effects of meaning generated by the practice of photoperformance, taken in terms of the historical intertwining of the two arts represented there. To this end, the work of contemporary Brazilian artist Berna Reale was elected. Theoretically, the dissertation takes the perspective of the concepts of punctum, studium, photographic paradox and myth, as formulated by Roland Barthes and his scholars. Appropriately, it also includes works on the issue of performance art and photoperformance presented by Philip Ausslander, on a documentary and theatrical level; and Luciano Vinhosa, in the field of collage, montage and mise-en-scène. But in compliance with the specific context of the artistic production in focus, it also subsidiarily handles the concepts of Amazonian visuality in Orlando Maneschy and Marisa Mokarzel; semiotic conversion in João de Jesus Paes Loureiro; capitalistic culture in Félix Guattari and Suely Rolnik; and the relationship between periphery and multinationalized media images in Gil Vieira Costa. The analyzed corpus is made up of a section of Berna Reale's work consisting of pieces gathered in the solo exhibition “While you laugh”, held at the Nara Roesler gallery, in New York City in 2019, curated by art critic and researcher Claudia Calirman. Added to the artist's recognition, the relevance of the research is linked to the opportunity to apply to her disturbing production Barthes' inquiry into the limits between codification and semioclasm, mythical construction and the dimension of presence in photography